Mathematical modelling of a crop irrigation problem - Ramathas, Rishi (Nanyang Technological University, 2022)
When cultivating row crops in low-rainfall locations, the furrow irrigation method is widely utilized. To maximize furrow design, it is necessary to simulate the furrow irrigation system. The goal of this study was to apply the boundary element approach to simulate a two-dimensional steady-state periodic furrow irrigation system for an agricultural soil compound consisting of a mixture of equal parts of sand, silt and clay. For general furrow form, a boundary element approach was designed to estimate the soil suction potential. Following that, numerical solutions were found for flat, rectangular, semicircular, and parabolic furrows. The exact solution and the numerical solution for the flat furrow scenario coincided quite well. Other examples' solutions likewise demonstrated convergence and symmetry, which was predicted. This suggests that the boundary element model formulation was accurate.